2015
DOI: 10.1186/s40479-015-0025-x
|View full text |Cite
|
Sign up to set email alerts
|

Rejection sensitivity and symptom severity in patients with borderline personality disorder: effects of childhood maltreatment and self-esteem

Abstract: BackgroundInterpersonal dysfunction in Borderline Personality Disorder (BPD) is characterized by an ‘anxious preoccupation with real or imagined abandonment’ (DSM-5). This symptom description bears a close resemblance to that of rejection sensitivity, a cognitive affective disposition that affects perceptions, emotions and behavior in the context of social rejection. The present study investigates the level of rejection sensitivity in acute and remitted BPD patients and its relation to BPD symptom severity, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 78 publications
7
45
0
1
Order By: Relevance
“…The domains of social rejection sensitivity, provocation of aggressive behaviour, and inability to become involved in trustful and cooperative behaviour stand out as particularly important (for a review, see [108]). In adult BPD patients, the experience of being socially excludedmainly under experimental conditions [109]-leads to distorted perceptions of others, as expressed in feelings such as contempt, resentment and anger towards others [110,111]. Similar to findings in adults, a recent study in adolescent BPD patients found that, compared with normal controls, they experienced negative emotions more intensely in a social exclusion paradigm; however, there were no differences in their pattern of responding [112].…”
Section: Psychological Mechanismsmentioning
confidence: 77%
“…The domains of social rejection sensitivity, provocation of aggressive behaviour, and inability to become involved in trustful and cooperative behaviour stand out as particularly important (for a review, see [108]). In adult BPD patients, the experience of being socially excludedmainly under experimental conditions [109]-leads to distorted perceptions of others, as expressed in feelings such as contempt, resentment and anger towards others [110,111]. Similar to findings in adults, a recent study in adolescent BPD patients found that, compared with normal controls, they experienced negative emotions more intensely in a social exclusion paradigm; however, there were no differences in their pattern of responding [112].…”
Section: Psychological Mechanismsmentioning
confidence: 77%
“…There was less consistency in outcomes on other forms of abuse. Five studies indicated physical abuse significantly correlated with RS (Bungert, Liebke, et al ., ; Erozkan, ; Feldman & Downey, ; Hernandez, Trout, & Liu, ; Kahya, ), and three studies indicated physical neglect correlated significantly (Bungert, Liebke, et al ., ; Goodman, Fertuck, Chesin, Lichenstein, & Stanley, ; Kahya, ). However, one study reported no significant relationship between physical abuse and RS in a non‐clinical population (Goodman et al ., ) and another reported no significant relationship between physical abuse or neglect in a mixed population (Masland, ).…”
Section: Resultsmentioning
confidence: 98%
“…Emotional abuse and/or neglect (EAN) consistently correlated with RS in a non‐clinical sample despite study quality, with typically moderate effect sizes though the range was large ( r = .17 to .49). Two studies considered the overall CTQ and found significant moderate correlations (Bungert, Liebke, et al ., ; Kahya, ). There was less consistency in outcomes on other forms of abuse.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…On the domains of self-image is the construct of self-esteem, which is usually low in BPD patients (James, 1890;Kanter, 2001). According to Bungert and colleagues (Bungert et al, 2015) rejection sensitivity is an important component in BPD and seems to be related with low self-esteem and BPD symptom severity. Self-esteem is described as "how you evaluate yourself" and is considered part the construct named self-concept "your ideas about yourself" and this last one part of what is known by identity "who you are" (Baumeister, 1999).…”
Section: Introductionmentioning
confidence: 99%